Effectiveness and cost-effectiveness of an integrated digital psychological intervention (EmoEase) in Chinese chronic obstructive pulmonary disease patients: study protocol of a randomized controlled trial - Chen, Simiao; Chen, Wenjin; Li, Yanfei; Yu, Yiwen; Chen, Qiushi; Jiao, Lirui; Huang, Ke; Tong, Xunliang; Geldsetzer, Pascal; Bunker, Aditi; Fang, Xingyuan; Jing, Shu; et al. (Digital health, 2024)
Background - Mental health problems in patients with chronic obstructive pulmonary disease (COPD) are common and frequently neglected. Digital psychological interventions may reduce mental health problems, but their effectiveness has not been evaluated in the Chinese COPD population. In this study, we will develop an integrated digital psychological intervention (EmoEase) and evaluate its effectiveness and cost-effectiveness in enhancing the mental wellbeing of patients with COPD in China. - Methods - This study is a multicenter, two-arm, randomized controlled trial (RCT) with a parallel-group design to enroll at least 420 patients with COPD with age over 35 years. Participants will be assigned to receive either usual care (control group) or usual care + EmoEase (intervention group). Assessments will take place at baseline (T0) and 4 weeks (T1), 8 weeks (T2), and 16 weeks (T3) after baseline, and participants will be asked to complete questionnaires and physical measurements. The primary outcome measure will assess mental wellbeing using the Warwick Edinburgh Mental Wellbeing Scale (WEMWBS). Secondary outcome measures will assess mental health, physical health, COPD symptoms, health risk behaviors, socioeconomic indicators, and healthcare utilization and expenditure. Analyses will utilize an intention-to-treat approach. - Discussion - This is the first RCT to examine the value of EmoEase, a novel digital psychological intervention for patients with COPD. If this intervention is effective and cost-effective, it could be rapidly scaled up to provide mental healthcare for patients with COPD in China. - Trial registration - ClinicalTrials.gov Identifier: NCT06026709. Date of first submission: 30 August 2023. https://clinicaltrials.gov/study/NCT06026709